Akar Politik Identitas di Indonesia - Sofi Mubarok (Jisiera: The Journal of Islamic Studies and International Relations, 2023)
In the last decade, identity politics has become a central theme in political discourse in Indonesia. The peak was when the DKI Jakarta Gubernatorial Election was held in 2017. The emergence of the issue of the use of identity politics that carried religion and ethnicity caused various debates among intellectuals and the public. Using Michel Foucault's concepts of power and knowledge, this paper uncovers and analyzes the processes and debates behind the re-emergence of identity politics in Indonesia. Using a literature study approach, this research proves that identity politics in Indonesia existed even before the era of independence. This means that this is not something new and also that Indonesia's political experience has always been able to handle this situation. Keywords: Identity, Politics, Islam, Power, History, Indonesia